Carbon Quantum Dot Modified Reduced Graphene Oxide Framework for Improved Alkali Metal Ion Storage Performance. Issue 35 (4th August 2022) - Jin, Shikai; Allam, Omar; Lee, Kyungbin; Lim, Jeonghoon; Lee, Michael J.; Loh, Sze Hou; Jang, Seung Soon; Lee, Seung Woo
Abstract: Organic materials with redox‐active oxygen functional groups are of great interest as electrode materials for alkali‐ion storage due to their earth‐abundant constituents, structural tunability, and enhanced energy storage properties. Herein, a hybrid carbon framework consisting of reduced graphene oxide and oxygen functionalized carbon quantum dots (CQDs) is developed via the one‐pot solvothermal reduction method, and a systematic study is undertaken to investigate its redox mechanism and electrochemical properties with Li‐, Na‐, and K‐ions. Due to the incorporation of CQDs, the hybrid cathode delivers consistent improvements in charge storage performance for the alkali‐ions and impressive reversible capacity (257 mAh g −1 at 50 mA g −1 ), rate capability (111 mAh g −1 at 1 A g −1 ), and cycling stability (79% retention after 10 000 cycles) with Li‐ion. Furthermore, density functional theory calculations uncover the CQD structure‐electrochemical reactivity trends for different alkali‐ion. The results provide important insights into adopting CQD species for optimal alkali‐ion storage. Abstract : The hybrid carbon framework consisting of reduced graphene oxide and oxygen functionalized carbon quantum dots prevents graphitic restacking and exhibits more reversible oxygen redox sites. Owing to the incorporation of carbon quantum dots, the hybrid cathode delivers impressive improvements in charge storage performance as a cathode material with Li‐, Na‐, and K‐ions.